2019
DOI: 10.1002/jcla.22878
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the BioPlex 2200 syphilis total screen (IgG/IgM) with reflex to an automated rapid plasma reagin test

Abstract: BackgroundWe evaluated the recently FDA cleared BioPlex 2200 Syphilis Total Screen and automated rapid plasma reagin (RPR) assay for the detection of total (IgG/IgM) treponemal and non‐treponemal antibodies in the reverse syphilis algorithm.MethodsProspectively submitted samples (n = 885) were assayed by both the IgG/IgM BioPlex Syphilis Screen and the original IgG BioPlex Syphilis Screen. The IgG screen reactive samples were reflexed to traditional RPR, and IgG/IgM screen reactive samples were reflexed to the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 9 publications
(21 reference statements)
0
4
0
Order By: Relevance
“…[17][18][19][20][21] More recently, Bioplex 2200 integrated a treponemal and RPR assay on one analyzer with reported sensitivities for RPR ranging from 90.0% to 96.2%. 12,[22][23][24][25] A limitation of Bioplex 2200 RPR is the need for manual predilution of samples with titers <1:4 or >1:64. Next to AIX1000 and Bioplex 2200, also the ASI Evolution was approved by the Food and Drug Administration in 2020 for automated RPR analysis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[17][18][19][20][21] More recently, Bioplex 2200 integrated a treponemal and RPR assay on one analyzer with reported sensitivities for RPR ranging from 90.0% to 96.2%. 12,[22][23][24][25] A limitation of Bioplex 2200 RPR is the need for manual predilution of samples with titers <1:4 or >1:64. Next to AIX1000 and Bioplex 2200, also the ASI Evolution was approved by the Food and Drug Administration in 2020 for automated RPR analysis.…”
Section: Discussionmentioning
confidence: 99%
“…Other automated RPR assays such as Mediace, HiSens Auto RPR, and Sekure RPR have been developed previously, but sensitivities were lower when compared with manual RPR 17–21 . More recently, Bioplex 2200 integrated a treponemal and RPR assay on one analyzer with reported sensitivities for RPR ranging from 90.0% to 96.2% 12,22–25 . A limitation of Bioplex 2200 RPR is the need for manual predilution of samples with titers <1:4 or >1:64.…”
Section: Discussionmentioning
confidence: 99%
“…Biological false positive, although uncommon, must be considered during pregnancy or autoimmune illnesses as well as other infectious diseases. Currently, NTT are manually performed and several attempts to automate these tests have been described [42]. Monitoring of nontreponemal test titer should be done using the same test and it is indicated to:…”
Section: Indirect Methodsmentioning
confidence: 99%
“…They concluded that the addition of the detection of treponemal IgM antibodies to the IgG/IgM screen had not significantly affected the sensitivity and specificity compared to the original IgG screen. But the addition of the comparable BioPlex RPR assay to the instrumentation significantly reduced the overall labor of syphilis screening and confirmation [72].…”
Section: Modern Serologic Diagnosticmentioning
confidence: 99%